2015
DOI: 10.17219/acem/29264
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Valproic Acid on Primary Chronic Lymphocytic Leukemia Cells

Abstract: Background. Chronic lymphocytic leukemia (CLL) is the most common adult leukemia in western civilization. The accumulation of CD5 + CD19 + B lymphocytes in peripheral blood is due to a defect in the apoptotic pathway rather than excessive proliferation in the bone marrow and lymph nodes. Despite a number of treatments, CLL remains an incurable disease. Valproic acid (VPA) activity, as a histone deacetylase inhibitor, could restore the epigenetic changes underlying the pathogenesis of CLL and thus induce cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Several studies have shown the effect of lithium on cytokine production by monocytes in breast cancer patients 15 17 . Meanwhile, valproic acid is mainly known for its antileukemic properties; it induces apoptosis of chronic lymphocytic leukemia cells 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the effect of lithium on cytokine production by monocytes in breast cancer patients 15 17 . Meanwhile, valproic acid is mainly known for its antileukemic properties; it induces apoptosis of chronic lymphocytic leukemia cells 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocyte doubling time longer than 12 months is usually associated with a mild course of CLL; however, the shorter the LDT, the more aggressive is the phenotype of the disease. [6][7][8][9] The concentration of beta-2 microglobulin is another established prognostic factor: the higher the value of this parameter, the worse is the prognosis. 10 Chronic lymphocytic leukemia cells differ in terms of the mutational status of genes encoding immunoglobulin heavy chain variable (IgVH), which is correlated with the intracellular expression of ζ-associated protein-70 (ZAP-70), the presence of the CD38 antigen and the degree of activation and susceptibility to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients submitted to CCRT and VPA experienced a higher rate of medullary toxicity and infection than reported in the literature and historical control data from our institution [29]. A possible synergistic effect of VPA and CCRT in the observed lymphopenia might have occurred, leading to the exacerbated toxicity in this trial [38,39]. Somnolence was frequent, however, manageable and there was no apparent compromise in quality of life.…”
Section: Discussionmentioning
confidence: 56%